ANALYSIS OF FACTORS AFFECTING THE WAITING PERIOD OF EDUCATED WORKERS - Made Violita Rahmawati; I Wayan Wenagama (Buletin Studi Ekonomi, 2025)
Educated unemployed are the population of the labor force who do not yet have a job but have completed the upper secondary level of education. Currently the level of education is no longer a reference to get a job quickly, there are many other factors that can affect the time to get a job. This study aims to analyze the effect of education level, age, gender and training experience on the waiting period of educated workers in Denpasar City. This study used data sourced from the August 2022 Denpasar City Sakernas questionnaire and involved 895 communities as samples. The data were analyzed using SPSS based on multiple linear regression techniques. The results showed that university graduates had a shorter waiting period than high school graduates, age positively affected the waiting period, gender did not affect the waiting period, respondents who had training experience had a shorter waiting period than those who did not have training experience. Based on the results of the study, it is expected that the local government will be able to balance the harmony between education and labor demand, open more jobs, and increase human resources.